2017
DOI: 10.18203/2320-1770.ijrcog20173498
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to compare the efficacy of preinduction with mifepristone 12 hours versus 24 hours prior for second trimister pregnancy termination

Abstract: INTRODUCTIONIn spite of abortion being legal in India, 8-18% maternal deaths are due to abortion.1 Second trimester termination rate is increased now because of increased detection of structural, genetic and metabolic disorders.2 It is responsible for 2/3 rd of major abortion related complications. Various surgical and medical methods have been tried for the second trimester MTP with varying success and induction abortion interval. Among them combination of mifepristone and misoprostol has been most widely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In the present study, 98 % of group A and 88 % of group B had a complete abortion which is statistically significant with a p-value < 0.03 and is comparable to a study done by Akkenapally P. L. [12] where 96 % had a complete abortion in mifepristone primed group and 89 % in misoprostol alone group. In a study by Patel U et al [13], the complete abortion rate was 100 % in the mifepristone-induced group and 84 % in the misoprostol-alone group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, 98 % of group A and 88 % of group B had a complete abortion which is statistically significant with a p-value < 0.03 and is comparable to a study done by Akkenapally P. L. [12] where 96 % had a complete abortion in mifepristone primed group and 89 % in misoprostol alone group. In a study by Patel U et al [13], the complete abortion rate was 100 % in the mifepristone-induced group and 84 % in the misoprostol-alone group.…”
Section: Discussionsupporting
confidence: 87%
“…In a study done by Nagaria et al [10] showed there is a significant reduction in the dose of misoprostol required for completeness of abortion in a mifepristone-primed group with a p-value of <0.001. In a study by Patel U et al [12], the dose required for the mifepristone pre-induced group was 122 mcg, and in the misoprostol alone group, it was 696 mcg.…”
Section: Discussionmentioning
confidence: 99%